Interleukin-1β Inhibition for Chronic Kidney Disease in Obese Mice With Type 2 Diabetes - Lei, Yutian; Devarapu, Satish K.; Motrapu, Manga; Cohen, Clemens D.; Lindenmeyer, Maja T.; Moll, Solange; Kumar, Santhosh V.; Anders, Hans-Joachim (Frontiers in Immunology, 2019)
Inflammasome-driven release of interleukin(IL)-1β is a central element of many forms of sterile inflammation and has been evident to promote the onset and progression of diabetic kidney disease. We microdissected glomerular and tubulointerstitial samples from kidney biopsies of patients with diabetic kidney disease and found expression of IL-1β mRNA. Immunostaining of such kidney biopsies across a broad spectrum of diabetic kidney disease stages revealed IL-1β positivity in a small subset of infiltrating immune cell. Thus, we speculated on a potential of IL-1β as a therapeutic target and neutralizing the biological effects of murine IL-1β with a novel monoclonal antibody in uninephrectomized diabetic db/db mice with progressive type 2 diabetes- and obesity-related single nephron hyperfiltration, podocyte loss, proteinuria, and progressive decline of total glomerular filtration rate. At 18 weeks albuminuric mice were randomized to intraperitoneal injections with either anti-IL-1β or control IgG once weekly for 8 weeks. During this period, anti-IL-1β IgG had no effect on food or fluid intake, body weight, and fasting glucose levels. At week 26, anti-IL-1β IgG had reduced renal mRNA expression of kidney injury markers (Ngal) and fibrosis (Col1, a-Sma), significantly attenuated the progressive decline of glomerular filtration rate, and preserved podocyte number without affecting albuminuria or indicators of single nephron hyperfiltration. No adverse effect were observed. Thus, IL-1β contributes to the progression of chronic kidney disease in type 2 diabetes and might therefore be a valuable therapeutic target, potentially in combination with drugs with different mechanisms-of-action such as RAS and SGLT2 inhibitors.